Acellular human placenta small-diameter vessels as a favorable source of super-microsurgical vascular replacements: a proof of concept - Falkner, Florian; Mayer, Simon Andreas; Thomas, Benjamin; Zimmermann, Sarah Onon; Walter, Sonja; Heimel, Patrick; Thiele, Wilko; Sleeman, Jonathan P.; Bigdeli, Amir Khosrow; Kiss, Herbert; Podesser, Bruno Karl; Kneser, Ulrich; et al. (Bioengineering, 2023)
In this study, we aimed to evaluate the human placenta as a source of blood vessels that can be harvested for vascular graft fabrication in the submillimeter range. Our approach included graft modification to prevent thrombotic events. Submillimeter arterial grafts harvested from the human placenta were decellularized and chemically crosslinked to heparin. Graft performance was evaluated using a microsurgical arteriovenous loop (AVL) model in Lewis rats. Specimens were evaluated through hematoxylin-eosin and CD31 staining of histological sections to analyze host cell immigration and vascular remodeling. Graft patency was determined 3 weeks after implantation using a vascular patency test, histology, and micro-computed tomography. A total of 14 human placenta submillimeter vessel grafts were successfully decellularized and implanted into AVLs in rats. An appropriate inner diameter to graft length ratio of 0.81 ± 0.16 mm to 7.72 ± 3.20 mm was achieved in all animals. Grafts were left in situ for a mean of 24 ± 4 days. Decellularized human placental grafts had an overall patency rate of 71% and elicited no apparent immunological responses. Histological staining revealed host cell immigration into the graft and re-endothelialization of the vessel luminal surface. This study demonstrates that decellularized vascular grafts from the human placenta have the potential to serve as super-microsurgical vascular replacements.
Gesehen am 25.04.2023